Beneficial In Vivo Effect of Aripiprazole on Neuronal Regeneration Following Neuronal Loss in the Dentate Gyrus: Evaluation Using a Mouse Model of Trimethyltin-Induced Neuronal Loss/Self-Repair in the Dentate Gyrus - Masanori Yoneyama; Shigeru Hasebe; Noriko Kawamoto; Tatsuo Shiba; Taro Yamaguchi; Maho Kikuta; Makoto Shuto; Kiyokazu Ogita (Elsevier, 2014)
Abstract.: Aripiprazole is used clinically as an atypical antipsychotic. We evaluated the effect of in vivo treatment with aripiprazole on the proliferation and differentiation of neural stem/progenitor cells in a mouse model, trimethyltin-induced neuronal loss/self-repair in the hippocampal dentate gyrus (referred as "impaired animals") [Ogita et al., J Neurosci Res. 82, 609 - 621 (2005)]. In the impaired animals, an increased number of 5-bromo-2'-deoxyuridine (BrdU)-positive cells was seen in the dentate gyrus at the initial time window of the self-repair stage. At the same time window, a single treatment with aripiprazole significantly increased the number of cells positive for both BrdU and nestin in the dentate gyrus of the impaired animals. Chronic treatment with aripiprazole promoted the proliferation/survival and neuronal differentiation of the cells newly-generated following the neuronal loss in the dentate gyrus of the impaired animals. The chronic treatment with aripiprazole improved depression-like behavior seen in the impaired animals. Taken together, our data suggest that aripiprazole had a beneficial effect on neuronal regeneration following neuronal loss in the dentate gyrus through indirectly promoted proliferation/survival and neuronal differentiation of neural stem/progenitor cells in the subgranular zone of the dentate gyrus. Keywords:: aripiprazole, dentate gyrus, neural stem/progenitor cell, neurogenesis, trimethyltin